The Shadow Costs of Illiquidity - Jansen, Kristy A. E.; Werker, Bas J. M. (Journal of Financial and Quantitative Analysis, 2022)
Abstract We solve a flexible model that captures transactions costs and infrequencies of trading opportunities for illiquid assets to better understand the shadow costs of illiquidity for different origins of asset illiquidity and heterogeneous investor types. We show that illiquidity that results in suboptimal asset allocation carries low shadow costs, whereas these costs are high when illiquidity restricts consumption. As a result, the shadow costs are high for short-term investors, investors who face substantial liquidity shocks, and investors who desire to allocate a large fraction of their wealth to illiquid assets.